2011
DOI: 10.2134/jeq2010.0009
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Cycles of Dissolved Oxygen and Nitrous Oxide in Rivers along a Trophic Gradient in Southern Ontario, Canada

Abstract: Diel (24-h) cycling of dissolved O2 (DO) in rivers is well documented, but evidence for coupled diel changes in DO and nitrogen cycling has only been demonstrated in hypereutrophic systems where DO approaches zero at night. Here, we show diel changes in N2O and DO concentration at several sites across a trophic gradient. Nitrous oxide concentration increased at night at all but one site in spring and summer, even when gas exchange was rapid and minimum water column DO was well above hypoxic conditions. Diel N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…Our results suggest a mean error of ∼6%, but as high as 28%. Error associated with O 2 -based estimates of gas transfer is similar to tracer-based measurements, or higher [Rosamond et al, 2011]. Where we had multiple measurements of gas transfer at different stream discharges, we found relatively good agreement between measured and modeled gas transfer coefficient in the Black River (1-3% difference between measured and modeled) and Stouffville Creek (1-22%), but poorer results in Jackson Creek (13-44%), Mariposa Brook (30-41%), and Layton Creek (38-42%).…”
Section: Sources Of Errormentioning
confidence: 89%
“…Our results suggest a mean error of ∼6%, but as high as 28%. Error associated with O 2 -based estimates of gas transfer is similar to tracer-based measurements, or higher [Rosamond et al, 2011]. Where we had multiple measurements of gas transfer at different stream discharges, we found relatively good agreement between measured and modeled gas transfer coefficient in the Black River (1-3% difference between measured and modeled) and Stouffville Creek (1-22%), but poorer results in Jackson Creek (13-44%), Mariposa Brook (30-41%), and Layton Creek (38-42%).…”
Section: Sources Of Errormentioning
confidence: 89%
“…Rosamond et al (2012) reported that N 2 O was largely produced by denitrification in hypoxic or anoxic sediment in the Grand River where widespread hypoxia rather than increasing N exports may lead to increased N 2 O emission. In contrast to NO À 3 , several investigators have demonstrated a negative correlation between DO and dissolved N 2 O (Yoshinari, 1976;Zhan and Chen, 2006;Rosamond et al, 2011Rosamond et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in the EF 5r can be attributed to a scarcity of studies (21,22), poorly constrained water-air gaseous exchange relationships (23,24), and high variability in river morphology (25,26). Further, the EF 5r assumes a linear relation between nitrate in water and N 2 O emissions (14), the validity of which is the subject of considerable debate (27)(28)(29)(30). Finally, N 2 O fluxes derived from simple gas exchange models have been shown to underestimate the flux if stream channel hydraulics (i.e., stream flow velocity) are ignored (31), highlighting that stream chemistry alone is not an accurate predictor of N 2 O fluxes.…”
mentioning
confidence: 99%